1995
DOI: 10.1007/bf01962574
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic muscle profile types in response to pelvic muscle exercise

Abstract: Abstract:The purpose of this research was to describe the contractile response of pelvic muscle to exercise (PME). Pelvic muscle pressure curves from ten randomly selected records from a larger study of 65 women with urodynamically demonstrated stress urinary incontinence (SUI) were analyzed. The subjects completed a PME protocol that lasted 16 weeks. Five pressure curves before and after 16 weeks of exercise were analyzed and classified according to pressure-time profile types. Descriptive statistics revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Taylor and Henderson [1986] used surface EMG, and showed in a small study (N ¼ 13) that, urine loss decreased as PFM function increased. Boyington et al [1995], measuring vaginal squeeze pressure, did not ¢nd a correlation between increase in muscle strength and improvement in leakage. However, after dividing Sumscore is obtained by adding points for the following parameters: change of negative closure pressure to positive during cough, improvement measured by pad test, score 4 or 5 on patient's own assessment, improvement measured by leakage index, improvement measured by social activity index.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Taylor and Henderson [1986] used surface EMG, and showed in a small study (N ¼ 13) that, urine loss decreased as PFM function increased. Boyington et al [1995], measuring vaginal squeeze pressure, did not ¢nd a correlation between increase in muscle strength and improvement in leakage. However, after dividing Sumscore is obtained by adding points for the following parameters: change of negative closure pressure to positive during cough, improvement measured by pad test, score 4 or 5 on patient's own assessment, improvement measured by leakage index, improvement measured by social activity index.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, Bump et al [1991] showed that only 49% of the women able to contract the PFM performed a contraction e¡ective enough to increase urethral pressure. This may explain why some authors have failed to ¢nd correlation between increased vaginal pressure and reduction of leakage [Hahn et al, 1991;Dougherty et al, 1993;Boyington et al, 1995]. On the other hand, measurement of voluntary contraction in a supine position may not be a valid assessment of automatic co-contraction during increase in abdominal pressure in an upright position.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Boyington et al [34] studied the PM response to PME in 10 women (mean age 51.7 years) who participated in a larger study of 65 women with SUI [32]. Graphic representations of voluntary PM contractions obtained before and after a 16-week PME program were analyzed according to pressure±time pro®les.…”
Section: Introductionmentioning
confidence: 99%